Assessment of some commercial feed brands in Nigeria on growth performance of Clarias gariepinus fingerlings (2016)
"This study assessed three commonly-available commercial catfish feed brands on growth, survival and nutrient utilization of Clarias gariepinus fingerlings under controlled conditions; providing information on the integrity and quality of some of the feeds in the market. C. gariepinus fingerlings (3.83± 0.22g) were fed to satiation twice daily at 9.00hr and 18.00hr with 2mm pellet size of three commercial diets scripted TD, TT, and TV in concrete tanks. Growth performance and nutrients utilization parameters were measured and calculated; water quality parameters were controlled using a partial flow-through system. ANOV A showed that there were significant differences (P<0.05) in the mean weight gain, specific growth rate, survival rate, food conversion rate, nitrogen metabolism and protein efficiency ratio. TV had the most significant value for mean weight gain (41.54 ± 4.09g), specific growth rate (1.65 ± 0.04g/day), feed conversion rate (0.7), nitrogen metabolism (951.91), and protein efficiency ratio (2.57) with 90.00 ± 5.0% survival rate; TD had significantly highest survival rate (92.50 ± 4.51%) with mean weight gain 36.77 ± 0.48g. Proximate analysis of TD, TT and TV revealed that macronutrients therein significantly different from the brands' claim, except TD. This study revealed that, for fast fish growth on less expensive feed desired by catfish farmers, commercial catfish feed brand tagged TV, was the best, giving a better growth performance and nutrient utilization, at 48.3% CP, 6.01% Fat, and 3.03% CF.